The Strategy of Monitoring Sea Project To Improve Competence Through Application Based Remote Methods - Amad Narto; Mungin Eddy Wibowo; Joko Sutarto; Abdurrahman Abdurrahman; Teguh Purnomo (International Conference on Science, Education, and Technology, 2023)
In the field of education, all aspects of education should align with the goals of national education. Education has a significant impact on human development, especially in the era of globalization, to develop academic skills, students' personalities, and mastery of knowledge and technology in accordance with the needs and developments of the working world. Politeknik Ilmu Pelayaran (PIP) Semarang is a vocational state university in the maritime field that implements a one-year full-time internship program for bachelor's and Diploma-IV degrees. This internship program, also known as sea practice, is carried out by cadets on board ships to apply the lessons they have learned during their maritime studies. During the sea practice, the institution continuously monitors the progress of the cadets from a distance to assess their performance during the internship period. In this era of globalization and digitization, information systems are rapidly developing. The integration of information can be implemented in sea practice to prevent and address the educational and maritime testing issues that often arise at the central, regional, and cadet levels. PIP Semarang provides remote monitoring facilities through an application-based system. The observations have shown that this monitoring method can enhance competence, communication, and problem-solving skills. In further development, the application will be aligned with the digitalization-based education management.